2011
DOI: 10.2174/138161211798220981
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein-60 and Risk for Cardiovascular Disease

Abstract: Cardiovascular disease (CVD) is a leading cause of morbidity and mortality worldwide. There is growing evidence that molecular chaperones, many of which are heat shock proteins HSPs, are involved in CVD pathogenesis. In this review we focus on HSP60, the human mitochondrial chaperone that also displays extramitochondrial and extracellular functions. HSP60 is typically cytoprotective but a number of stress conditions determine its conversion to a potentially toxic molecule for cells and tissues. We present illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 94 publications
1
29
1
1
Order By: Relevance
“…The actions of Hsp60 could lead to the modification of those proteins, and in this manner it could have a role in many diseases, including carcinogenesis. Heart Heart failure; Coronary vascular disease [137][138][139][140] Kidney Glomerulonephritis [141] Large bowel Inflammatory bowel diseases [19,142,143] Lung Chonic obstructive pulmonary disease [20] Oral cavity Periodontitis [144,145] Pancreas Type 1 diabetes [146][147][148][149][150][151] Skin Scleroderma, pemphigoid; Psoriasis; Dermatomyositis [152,153] Synovial joints Rheumatoid arthritis; Juvenile idiopathic arthritis [154][155][156][157] Vessels Vasculitis; Atherosclerosis [158][159][160][161][162][163][164][165][166][167] Adapted from [2]. Hsp60 seems to contribute to tumor cell survival, but this is controversial.…”
Section: Hsp60 Chaperonopathies and Chaperonotherapy: Targets And Agentsmentioning
confidence: 99%
“…The actions of Hsp60 could lead to the modification of those proteins, and in this manner it could have a role in many diseases, including carcinogenesis. Heart Heart failure; Coronary vascular disease [137][138][139][140] Kidney Glomerulonephritis [141] Large bowel Inflammatory bowel diseases [19,142,143] Lung Chonic obstructive pulmonary disease [20] Oral cavity Periodontitis [144,145] Pancreas Type 1 diabetes [146][147][148][149][150][151] Skin Scleroderma, pemphigoid; Psoriasis; Dermatomyositis [152,153] Synovial joints Rheumatoid arthritis; Juvenile idiopathic arthritis [154][155][156][157] Vessels Vasculitis; Atherosclerosis [158][159][160][161][162][163][164][165][166][167] Adapted from [2]. Hsp60 seems to contribute to tumor cell survival, but this is controversial.…”
Section: Hsp60 Chaperonopathies and Chaperonotherapy: Targets And Agentsmentioning
confidence: 99%
“…HSP60 is considered as a biomarker to be applied in diagnosis, prognosis and treatment response, as well as for prevention and treatment of cardiovascular diseases (Rizzo et al, 2011). Our study showed that workers with ECG abnormalities represented 34.3% of the total number of the exposed group.…”
Section: Resultsmentioning
confidence: 71%
“…HSP60 plays variable roles, most likely depending on the existing conditions at the cell or tissue level. HSP60 may play an antiatherogenic or a proatherogenic role, depending on currently unknown mechanisms (Rizzo et al, 2011). Ho et al (2012) found that serum HSP60 does not provide clinical significance as regards hearing outcome of sudden sensorineural hearing loss, but no research was found to be interested in associating HSP60 with NIHL.…”
Section: Introductionmentioning
confidence: 99%
“…Information about Hsp60 and activation of innate and adaptive immunities has been published and discussed elsewhere [35][36][37]. Here we concentrate on information about the specific humoral (antibody-mediated) immune response induced by Hsp60.…”
Section: Anti-hsp60 Antibodies: Danger or Safety?mentioning
confidence: 99%